2020
DOI: 10.1371/journal.pone.0229561
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiplex real-time PCR for rapid identification and quantitative analysis of Aspergillus species

Abstract: The identification of Aspergillus species and azole resistance is highly important for the treatment of invasive aspergillosis (IA), which requires improvements in current fungal diagnostic methods. We aimed to develop multiplex real-time PCR to identify major Aspergillus section and azole resistance. BenA and cyp51A genes were used to design primers, probes, and control DNA for multiplex PCR. Qualitative and quantitative analysis was conducted for 71 Aspergillus and 47 non-Aspergillus isolates. Further, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The pathogenicity assay results obtained here showed that the mango fruit is very susceptible to contamination with A. niger , and the type of injuries caused by fungal colonization is compatible with that described by other authors ( Kim et al, 2020 ; Shen et al, 2020 ). These results confirm the validity and applicability of this method for the study of the spoilage of mangoes by A. niger .…”
Section: Discussionsupporting
confidence: 91%
“…The pathogenicity assay results obtained here showed that the mango fruit is very susceptible to contamination with A. niger , and the type of injuries caused by fungal colonization is compatible with that described by other authors ( Kim et al, 2020 ; Shen et al, 2020 ). These results confirm the validity and applicability of this method for the study of the spoilage of mangoes by A. niger .…”
Section: Discussionsupporting
confidence: 91%
“…Real-time PCR targeting the fungal genome has also been used to identify fungal species in FFPE samples in several studies. [22][23][24][33][34][35] Some of these studies employed a multiple detection system for several fungi in FFPE samples. [22][23][24] A multiplex real-time PCR system targeting several fungal genomes showed an overall sensitivity of 64% for the identification of fungi from FFPE specimens.…”
Section: Discussionmentioning
confidence: 99%
“… 22‐24,33‐35 Some of these studies employed a multiple detection system for several fungi in FFPE samples. 22‐24 A multiplex real‐time PCR system targeting several fungal genomes showed an overall sensitivity of 64% for the identification of fungi from FFPE specimens. 24 The authors focused on filamentous fungi and succeeded in identifying Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the proposed method detected correctly all ten targeted pathogens, exhibited no cross-reactivity with nontargeted species and presented a limit of detection of 10 to 1 pg of DNA. The limit of detection in PCR assays is highly dependent on the method used to detect the amplified fragments, being much lower for pPCR and GeneScan analysis, in the range of pg to fg of DNA, compared with conventional electrophoresis (agarose or polyacrylamide gels), usually ng of DNA [ 39 ]. This multiplex panel for filamentous fungi was able to distinguish Aspergillus species and R. arrhizus, which has been a problem in other multiplex strategies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%